Consumer Trust and Online Travel Purchase Decisions in Digital Tourism: A Systematic Literature Review - Carnaval Rego Rio Sidabutar; Mochammad Fahmi; Akmil Asril; Bayu Wardhana (IJBLE Scientific Publications Community Inc., 2026)
Digital tourism increasingly depends on consumer confidence in platforms that mediate intangible, information-intensive, and security-sensitive transactions. However, the literature remains fragmented regarding the antecedents and behavioral functions of trust in online travel purchasing. This systematic literature review identifies the principal trust-related antecedents, examines the direct and mediating roles of trust, and maps unresolved research gaps. Following PRISMA 2020, 309 records were identified, 207 were screened after preliminary removal, 56 full-text reports were assessed for eligibility, and seven empirical studies were included in the thematic synthesis. The evidence clusters into three sets of trust-forming conditions: platform and service quality, social and informational cues, and consumer- or context-specific risk perceptions. Trust generally predicts purchase or repurchase intention and frequently mediates the effects of platform quality, authenticity, and flow experience. Nevertheless, its statistical influence is not uniform; in some settings, ratings, reviews, and e-service quality exert stronger effects. The evidence base is dominated by cross-sectional, single-platform studies and provides limited insight into post-purchase behavior and cross-market variation. Future research should employ comparative, longitudinal, and multi-platform designs and distinguish more clearly between trust as an antecedent, mediator, moderator, and outcome. For practitioners, transparent information, robust security, reliable service, and credible review systems remain central to sustainable digital tourism.